Current controversies in prenatal diagnosis 3: is there still a value in a nuchal translucency screening ultrasound in conjunction with maternal plasma non‐invasive cell‐free DNA testing?1. (10th December 2015) - Wilson, R. Douglas; Poon, Liona C.; Ghidini, Alessandro
Abstract : What's already known about this topic? Nuchal translucency is an ultrasound measurement of the fetal physiological lymphatic development as it can identify both normal and abnormal lymphatic collections. Abnormal or enlarged nuchal translucency measurements are nonspecific and heterogeneous in origin. The source of maternal plasma cell free fetal DNA is placental apoptosis. The embryonic and cellular development of the placenta can have true chromosomal mosaicism (involves fetus and placenta) orconfined placental mosaicism (CPM) (placenta only). CPM is present in 1–2% of placentas and can cause false positive results for diagnostic chorionic villus sampling and maternalplasma cell free DNA prenatal aneuploidy screening resultswhile false negative placental results are much less common at 1 per 3000. What does this study add? This report summarizes an oral debate presented at the 19th International Conference on Prenatal Diagnosis and Therapy inWashington, DC, USA, on 14 July 2015. This study compares the fetal aneuploidy screening and detection process with the ultrasound nuchal translucency aneuploidy-geneticpathology screening test/measurement and the more recent maternal plasma cell free DNA aneuploidy only screening test when used in conjunction or separately. Informed consent and patient understanding of the aneuploidy screening options and techniques is an important counselling principle for the variety of aneuploidy and genetic screening protocols.